Improving multiparametric MR‐transrectal ultrasound guided fusion prostate biopsies with hyperpolarized 13C pyruvate metabolic imaging: A technical development study. Issue 6 (17th August 2022) - Chen, Hsin‐Yu; Bok, Robert A.; Cooperberg, Matthew R.; Nguyen, Hao G.; Shinohara, Katsuto; Westphalen, Antonio C.; Wang, Zhen J.; Ohliger, Michael A.; Gebrezgiabhier, Daniel; Carvajal, Lucas; Gordon, Jeremy W.; Larson, Peder E. Z.; et al.
Abstract : Purpose: To develop techniques and establish a workflow using hyperpolarized carbon‐13 ( 13 C) MRI and the pyruvate‐to‐lactate conversion rate (kPL ) biomarker to guide MR‐transrectal ultrasound fusion prostate biopsies. Methods: The integrated multiparametric MRI (mpMRI) exam consisted of a 1‐min hyperpolarized 13 C‐pyruvate EPI acquisition added to a conventional prostate mpMRI exam. Maps of kPL values were calculated, uploaded to a picture archiving and communication system and targeting platform, and displayed as color overlays on T2 ‐weighted anatomic images. Abdominal radiologists identified 13 C research biopsy targets based on the general recommendation of focal lesions with kPL  >0.02(s −1 ), and created a targeting report for each study. Urologists conducted transrectal ultrasound‐guided MR fusion biopsies, including the standard 1 H–mpMRI targets as well as 12–14 core systematic biopsies informed by the research 13 C‐kPL targets. All biopsy results were included in the final pathology report and calculated toward clinical risk. Results: This study demonstrated the safety and technical feasibility of integrating hyperpolarized 13 C metabolic targeting into routine 1 H–mpMRI and transrectal ultrasound fusion biopsy workflows, evaluated via 5 men (median age 71 years, prostate‐specific antigen 8.4 ng/mL, Cancer of the Prostate Risk Assessment score 2) on active surveillance undergoing integrated scan and subsequent biopsies. No adverse event was reported. Median turnaround time was less than 3 days from scan to 13 C‐kPL targeting, and scan‐to‐biopsy time was 2 weeks. Median number of 13 C targets was 1 (range: 1–2) per patient, measuring 1.0 cm (range: 0.6–1.9) in diameter, with a median kPL of 0.0319 s −1 (range: 0.0198–0.0410). Conclusions: This proof‐of‐concept work demonstrated the safety and feasibility of integrating hyperpolarized 13 C MR biomarkers to the standard mpMRI workflow to guide MR‐transrectal ultrasound fusion biopsies.